Social support as a mediator in the relationship between job insecurity and psychological well-being among employees in public and private sectors - Wan Shahrazad Wan Sulaiman; Mohammad Rahim Kamaludin; Zainah Ahmad Zamani; Rozainee Khairudin; Fatimah Wati Halim (Penerbit Universiti Kebangsaan Malaysia, 2020)
Job insecurity influences employees’ effectiveness at work as they face uncertainty about their future. The objective of this study therefore, is to examine the relationship between job insecurity, social support and, psychological well-being. In addition, this study also investigates the role of social support in mediating the relationship between job insecurity and psychological well-being. A total of 1188 respondents from both public and private sectors consisting of 571 males and 617 females were involved in this study. A set of questionnaire was used to collect data and this questionnaire included the adapted Job Insecurity Scale, Multidimensional Scale of Perceived Social Support (MSPSS) and Psychological Well-being Scale. Results showed that there was a significant and negative correlation between job insecurity and psychological well-being, a significant and negative correlation between job insecurity and social support, and a positive and significant correlation between social support and psychological well-being. Regression analysis on the other hand, found that social support significantly mediated the relationship of job insecurity on psychological well-being. The findings indicated the importance of social support in buffering the effect of job insecurity which in turn will influence psychological well-being.